Integrating Islamic Aspect for Achieving Local Wisdom Principles Design in Roof Shape of Mosque, Case Study: Demak Mosque - Andriani, Rofi; Rohiim, Itishom Abdu; Jannah, Ana Zuhrotul; Balqis, Fadiyah Rafidah; Samudro, Harida (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018, 2019)
The development of islamic religion in indonesia has a long history. Acculturation of cultures becomes one of interesting things to discuss. Demak Mosque is one of them, it is one of the oldest mosque on java island. The uniqueness of this mosque is from the building form and the history. This mosque has the uniqueness form of building and also its history. The building form has a strong local culture functioned as mosque. This study aims to determine the aspects of Islamic values contained in the roof of the Mosque Demak form that associated with local wisdom values. The method used is correlational, used to obtain explaination of linkage between islamic value with local value wisdom in Demak Mosque. This method is used to know clearly of both relationship, then the wisdom to be taken to be used in the future. This study uses qualitative research with descriptive analysis to explain the influence of the relationship of the two variabel in the object of study to fit with reality. The research result shows that application of the local wisdom value(s) on the roof of Demak Mosque can not be released from islamic value as an alignment. The islamic value on the roof of Demak Mosque as an alignment to the function as a worship place.To apply the local wisdom value(s) that has been adapted with islamic values.